2008
DOI: 10.1080/03630260802508384
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitude Toward the Hemoglobinopathies Premarital Screening Program in Saudi Arabia: Population-Based Survey

Abstract: Genetic screening is an important tool to control, minimize, and prevent genetic disorders. Saudi Arabia started the first national premarital screening (PMS) program to control inherited hemoglobin (Hb) disorders that are the most commonly inherited genetic disorders in the Kingdom of Saudi Arabia. The aim of this study was to assess the knowledge, perception, and attitude among the Saudi population about the PMS program through a questionnaire-based survey. A total of 1,047 candidates were included, divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
44
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 8 publications
8
44
1
1
Order By: Relevance
“…Even years after program implementation, the knowledge of premarital screening was good but not adequate 2123. In the current report, the overall marriage cancellation among at-risk marriages was 26.5% and increased to more than 50% in 2009.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Even years after program implementation, the knowledge of premarital screening was good but not adequate 2123. In the current report, the overall marriage cancellation among at-risk marriages was 26.5% and increased to more than 50% in 2009.…”
Section: Discussionmentioning
confidence: 55%
“…In the current report, the overall marriage cancellation among at-risk marriages was 26.5% and increased to more than 50% in 2009. In a recent survey (2008), more than 60% of the participants were in favor of canceling at-risk marriages 23. However, in another study among 129 at-risk candidates identified in premarital screening, only 2% cancelled their marriage proposals.…”
Section: Discussionmentioning
confidence: 98%
“…Nowadays, premarital screening and counseling (PMSC) became compulsory by law in many Arab countries including Egypt. (1,2,3) Consanguineous marriage is still high in Egypt (35.3%) especially among first cousins (86%). However, the frequency varies by region.…”
Section: Introductionmentioning
confidence: 99%
“…However, high-risk communities exhibit a positive attitude for premarital screening and couple with an already affected child for prenatal diagnosis (Al Sulaiman et al 2008). In the present study, based on the application of the Btheory of planned behavior^on beliefs and attitudes, it has been hypothesized that carrier screening and education among married and premarital individuals belonging to Bhigh risk communitiesŵ ill have far-reaching implications towards β-thalassemia prevention in the country.…”
mentioning
confidence: 87%